Transplantation of human mesenchymal stem cells in a non-autogenous setting for bone regeneration in a rabbit critical-size defect model - Niemeyer, Philipp; Szalay, Krisztián; Luginbühl, R.; Südkamp, N. P.; Kasten, Philip (Acta biomaterialia, 2010)
Human mesenchymal stem cells (hMSC) represent an attractive cell population for tissue engineering purposes. Furthermore, hMSC are described as immune privileged, and non-autogenous application seems possible. The current study examines the regeneration potential of hMSC after xenogenic transplantation compared with autogenous rabbit MSC in a critical-size bone defect. After isolation, hMSC and rabbit MSC were seeded on calcium-deficient hydroxyapatite (CDHA) and transplanted into a radial critical-size defect of New Zealand white rabbits. Defects were filled with a CDHA scaffold seeded with autogenous rabbit MSC, CDHA seeded with xenogenic hMSC or unseeded CDHA. An empty defect served as control group. Animals were sacrificed after 3months. Evaluation was performed using radiography, micro-computed tomography (μ-CT) and histology. In addition, a non-destructive four-point-bending test was performed in order to evaluate biomechanical stiffness. While autogenous MSC seeded on CDHA led to increased healing of critical-size bone defects from radiological (μ-CT; p=0.009) and histological (p=0.048) perspectives compared with unloaded CDHA, it was not possible to demonstrate analogous effects for the xenogenic transplantation of hMSC. The xenogenic treatment group displayed inferior results in all parameters compared with the autogenous MSC treatment group (histology p=0.041; μ-CT p=0.006; biomechanical testing p=0.017). Nevertheless, no local or systemic inflammatory response resulting from xenogenic transplantation was observed. While previous papers suggest the use of non-autogenous hMSC cells for tissue engineering purposes, the present results show inferior clinical results from transplantation of hMSC in a xenogenic setting compared with autogenous MSC.